Enantioselective Nitroso Aldol Reaction Catalyzed by a Chiral Phosphine–Silver Complex. Issue 32 (21st October 2016) - Yanagisawa, Akira; Lin, Yuqin; Takeishi, Akihiro; Yoshida, Kazuhiro
Abstract : A catalytic asymmetric O ‐nitroso aldol reaction of alkenyl trifluoroacetates with nitrosoarenes was achieved by using QuinoxP*· AgOAc [( R, R )‐QuinoxP* = (–)‐( R, R )‐2, 3‐bis( tert ‐butylmethylphosphino)quinoxaline] as the chiral precatalyst and N, N ‐diisopropylethylamine as the base precatalyst in the presence of methanol. Optically active α‐aminooxy ketones with up to 99 % ee were regioselectively obtained in moderate to high yields by the in situ generated chiral silver enolates. Abstract : An efficient, catalytic, enantioselective nitroso aldol reaction between alkenyl trifluoroacetates and nitrosoarenes is described. The use of in situ generated chiral silver methoxide as the chiral catalyst allows the synthesis of various nonracemic α‐aminooxy ketones with enantiomeric excess values up to 99 %. ( R, R )‐QuinoxP* = (–)‐( R, R )‐2, 3‐bis( tert ‐butylmethylphosphino)quinoxaline.